3d-Qsar Design of New Bcr-Abl Inhibitors Based on Purine Scaffold and Cytotoxicity Studies on Cml Cell Lines Sensitive and Resistant to Imatinib - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Bcr-Abl inhibitors such as imatinib have been used to treat chronic myeloid leukemia (CML). However, the efficacy of these drugs has diminished due to mutations in the kinase domain, notably the T315I mutation. Therefore, in this study, new purine derivatives were designed as Bcr-Abl inhibitors based on 3D-QSAR studies. Methods: A database of 58 purines that inhibit Bcr-Abl was used to construct 3D-QSAR models. Using chemical information from these models, a small group of new purines was designed, synthesized, and evaluated in Bcr-Abl. Viability assays were conducted on imatinib-sensitive CML cells (K562 and KCL22) and imatinib-resistant cells (KCL22-B8). In silico analyses were performed to confirm the results. Results: Seven purines were easily synthesized (7a–g). Compounds 7a and 7c demonstrated the highest inhibition activity on Bcr-Abl (IC50 = 0.13 and 0.19 μM), surpassing the potency of imatinib (IC50 = 0.33 μM). 7c exhibited the highest potency, with GI50 = 0.30 μM on K562 cells and 1.54 μM on KCL22 cells. The GI50 values obtained for non-neoplastic HEK293T cells indicated that 7c was less toxic than imatinib. Interestingly, KCL22-B8 cells (expressing Bcr-AblT315I) showed greater sensitivity to 7e and 7f than to imatinib (GI50 = 13.80 and 15.43 vs. >20 μM, respectively). In silico analyses, including docking and molecular dynamics studies of Bcr-AblT315I, were conducted to elucidate the enhanced potency of 7e and 7f. Thus, this study provides in silico models to identify novel inhibitors that target a kinase of significance in CML. © 2025 by the authors.